The role of environmental legislation in promoting sustainable mining in the Democratic Republic of Congo :a study of the Katanga Copper Belt - Banze, Frank Nkulu Mulunda (My University, 2019)
The study investigates the effectiveness of environmental legislation in protecting the environment and local community development in the Katanga Copper Belt. In answering the research questions, the study used qualitative research methods for data collection and understands the phenomenon of environmental degradation and community poverty. The study argues that environmental legislation is an important tool for environmental management aimed at reducing the impact of anthropogenic activities on the environment, protecting the natural resources and local communities. Nevertheless, environmental policies must be followed by the strong institution's framework and the collaboration of mining stakeholders to ensure that the policies put in place to protect the environment are not only developed but are effectively implemented for the promotion of sustainable mining practice. In the study of the case of the Katanga Copper Belt, the study found that, in spite of environmental and mining policies which capture the concept of sustainable development and emphasised the protection of the environment and the socio-economic development of the local community. There is a glaring failure of services of state who do not properly exercise their mission of implementation, monitoring and evaluation. Furthermore, there is no concrete socio-economic development plan for the communities in the Katanga Copper Belt. In addition, there is no indication that the various provincial government sanctions the non-compliance by mining operators of their operations contained in the specification, “yet required by the legislator to protect the environment and to boost the socio-economic development of the local entities within the framework of the protection and equitable redistribution of national wealth advocated by article 58 of the Constitution of the Democratic Republic of the Congo. In order to improve the implementation of environmental legislation in the mining sector of the Katanga Copper Belt for the promotion of sustainable mining practice, the study recommends a systematic management approach of institution and mining sector based on Knowledge dissemination, capacity building, transparency, enforced compliance and dissemination of obligation and right of all mining stakeholders.
A thesis submitted to the University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Doctor of Philosophy in the Department of Geography and Environmental Studies, Johannesburg 2019